An investigation into prospective memory in children with developmental dyslexia - Khan, Azizuddin (Frontiers in Psychology, 2014)
Developmental dyslexia hinders reading and writing acquisition of around 5-10 % of the children all over the world. However, little is known about role of prospective memory among dyslexics. Prospective memory is realization of delayed intention. Realization of delayed intention requires self initiated process. The present study explored the role of memory (prospective and retrospective memory), meta-memory and attention among dyslexic’s children. One hundred and fifteen children (51 dyslexics and 64 normal controls) participated in the study. Prospective and retrospective memory questionnaire, everyday attention questionnaire and meta-memory were administered on children. Analysis of variance was used to analyses the data. All the main effects were significant. Some interactions were also found to be significant. Results suggest that dyslexic’s performance on memory (prospective and retrospective memory) was worse than normal control. Meta-memory influences both dyslexics and normal control on prospective and retrospective memory. However, meta-memory affected dyslexics much more than normal control group. Similarly, significant differential effects were observed for simple, difficult and mixed attentional condition among between dyslexics and normal control. Dyslexic’s performance was deteriorated as compared to normal control group. The findings of the study are discussed in the light of the existing literature. Keywords: Meta-memory, Phoneme, Phonological awareness,and Visuo-spatial sktechpad